FAKTA SOSIAL: OBYEK PENELITIAN LINGUISTIK MODERN - Purwoko, Herudjati (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper is explanatory in nature. It forwards an argument that the subject matter of language research in the modern times must be based on parole as a technical term originally coined by Saussure. The term best refers to the nature of linguistic data in the form of language really executed (uttered) by its native speakers in actual interactions. The speakers, thus, are real (instead of ideal) people belonged to a certain linguistic community replete with socio-cultural values embedded in their language. Supported by in depth readings mostly taken from the classic works of Saussure, of selected American Descriptivist and of Sampson, this paper concludes that parole as the subject matter of language research is a social fact. Keywords: langue, parole, language as social fact, actual speakers, performance, competence